1984
DOI: 10.1212/wnl.34.11.1509
|View full text |Cite
|
Sign up to set email alerts
|

Pseudotumor cerebri caused by a synthetic vitamin A preparation

Abstract: Pseudotumor cerebri developed in a 14-year-old girl with nodulocystic acne, who was taking excessive amounts of a synthetic vitamin A derivative. Although hypervitaminosis A has reportedly caused pseudotumor, Accutane has not previously been implicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(20 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Multiple case reports found benign intracranial hypertension, or pseudotumor cerebri, characterized by headache, papilledema, and normal CT/MRI and CSF, in children and adults exposed to high levels of vitamin A (Alemayehu 1995;Gerber et al 1954;Gomber and Chellani 1996;Lombaert and Carton 1976;Marie and See 1954;Oliver and Havener 1958;Seigel and Spackman 1972;Selhorst et al 1984;Spector and Carlisle 1984). Selhorst (Selhorst et al 1984) reported that 5/50 patients with "idiopathic" pseudotumor cerebri were found by dietary history to be ingesting large amounts of Vitamin A in their diet.…”
Section: Class Effect: Neuropsychiatric Effects Of Vitamin Amentioning
confidence: 99%
“…Multiple case reports found benign intracranial hypertension, or pseudotumor cerebri, characterized by headache, papilledema, and normal CT/MRI and CSF, in children and adults exposed to high levels of vitamin A (Alemayehu 1995;Gerber et al 1954;Gomber and Chellani 1996;Lombaert and Carton 1976;Marie and See 1954;Oliver and Havener 1958;Seigel and Spackman 1972;Selhorst et al 1984;Spector and Carlisle 1984). Selhorst (Selhorst et al 1984) reported that 5/50 patients with "idiopathic" pseudotumor cerebri were found by dietary history to be ingesting large amounts of Vitamin A in their diet.…”
Section: Class Effect: Neuropsychiatric Effects Of Vitamin Amentioning
confidence: 99%
“…However, the primary mechanisms of agents known to cause PTC involves the alteration of CSF absorption by effects on either the pressure differential between the central nervous system and venous blood (increasing inflow), or the arachnoid villi (reducing outflow) [36]. The suggested mechanism of ATRA induced PTC is a toxic pathophysiological interaction between vitamin A derivatives and lipid constituents of the choroid plexus and arachnoid villi, resulting in inhibited CSF absorption and an increase in intracranial pressure [37]. Treatment of this condition is necessary to prevent the primary complication, blindness, secondary to progressive optic disc swelling and atrophy [38].…”
Section: Discussionmentioning
confidence: 99%
“…However, the primary mechanisms of agents known to cause PTC involves the alteration of CSF absorption by effects on either the pressure differential between the central nervous system and venous blood (increasing inflow), or the arachnoid villi (reducing outflow) [36]. The suggested mechanism of ATRA induced PTC is a toxic pathophysiological interaction between vitamin A derivatives and lipid constituents of the choroid plexus and arachnoid villi, resulting in inhibited CSF absorption and an increase in intracranial pressure [37].…”
Section: Discussionmentioning
confidence: 99%